Sistem varovanja tajnih podatkov v Republiki Sloveniji v luči demokratičnega zagotavljanja nacionalne varnosti - Prezelj, Iztok (Teorija in praksa, 2015)
The threat of the illegal disclosure of classified information requires every modern state to create an efficient protection system. Classified information protection demands a comprehensive approach that goes far beyond narrow system thinking. This article defines the concept of a comprehensive classified information protection system, incorporating legal and institutional elements, the criteria for classifying information, access criteria, time limits for classification and measures to withdraw classification, mechanisms for the protection of whistleblowers (if they disclose illegal activities) etc. Empirical study of the Slovenian case showed that this state has managed to create a fairly comprehensive protection system of classified information, but several pressing challenges remain to be tackled.
Keywords: Data protection; Javna varnost; nacionalna varnost; obveščevalna dejavnost; Public safety; Secret service; Slovenia; Slovenija; Tajna služba; tajni podatki; varovanje tajnih podatkov; Varstvo podatkov